If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+x+x-5-2=8+2x+x
We move all terms to the left:
6x+x+x-5-2-(8+2x+x)=0
We add all the numbers together, and all the variables
6x+x+x-(3x+8)-5-2=0
We add all the numbers together, and all the variables
8x-(3x+8)-7=0
We get rid of parentheses
8x-3x-8-7=0
We add all the numbers together, and all the variables
5x-15=0
We move all terms containing x to the left, all other terms to the right
5x=15
x=15/5
x=3
| 1-10n=1 | | (3x-24)+2x+(4x+11)=180 | | d4− 2=2 | | 115=-4-7n | | 2x-3=12-123 | | 4a-3a=20+7 | | 8(x+7=6(x-4) | | 6x+x+x-5-2=8x+x | | -3.2+v/5=15.7 | | 12+x=x4 | | 20x+19=7x-15 | | -12.6x-4.9x=-154x=154 | | -9=4u+3 | | 2x/10=2 | | M14=3x+1 | | 10-7a=66 | | 5(h+1)=6(h-2) | | X2+4=(x+1)(x+3) | | x/7−14=-12 | | 5(4-x)=20-5x | | 82=9v+10 | | 4+15h+15=19+15h | | 0.75x+4=-5 | | -3z+4=-6z+28 | | -3=7-2g | | 129=1+8x | | -130=-10v-10 | | -7x-5=-6x-25 | | 12-4y=2y+11 | | -10(n-1)=30 | | 46x^2-30=0 | | 3x|4+4=-5 |